1993
DOI: 10.1523/jneurosci.13-01-00181.1993
|View full text |Cite
|
Sign up to set email alerts
|

Multiple modes of N-type calcium channel activity distinguished by differences in gating kinetics

Abstract: In many neurons, N-type Ca2+ channels are a major Ca2+ entry pathway and strongly influence neurotransmitter release. We carried out cell- attached patch recordings (110 mM Ba2+ as charge carrier) to characterize the rapid opening and closing kinetics of N-type Ca2+ channel gating in frog sympathetic neurons. Single channels display at least three distinct patterns of gating, characterized as low-, medium- , and high-rho o modes on the basis of channel open probability (rho o) during depolarizing pulses to -10… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
72
2

Year Published

1993
1993
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 90 publications
(77 citation statements)
references
References 44 publications
3
72
2
Order By: Relevance
“…Thus, more than the inhibitory molecule (B,) showed little dependence on the one reluctant gating mode was required to achieve an adequate degree of desensitization while the forward rate constant for description of the data. This is in agreement with the singlebinding of inhibitory molecules (F,) showed a progressive dechannel results of Delcour et al (1993), who found three modcline as the extent of inhibition decreased during desensitization ulated gating modes based on measurements of single-channel (Table 1). However, the rate of dissociation of the second bound open time and open probability.…”
Section: Do Reblock Kinetics Vary With the Level Of Inhibition?supporting
confidence: 89%
“…Thus, more than the inhibitory molecule (B,) showed little dependence on the one reluctant gating mode was required to achieve an adequate degree of desensitization while the forward rate constant for description of the data. This is in agreement with the singlebinding of inhibitory molecules (F,) showed a progressive dechannel results of Delcour et al (1993), who found three modcline as the extent of inhibition decreased during desensitization ulated gating modes based on measurements of single-channel (Table 1). However, the rate of dissociation of the second bound open time and open probability.…”
Section: Do Reblock Kinetics Vary With the Level Of Inhibition?supporting
confidence: 89%
“…A detailed understanding of this important feature of IP 3 R behavior is therefore crucial for unraveling the complexity of Ca 2+ signaling and its role in cell function and disease. Modal gating has been observed in the kinetics of many other ion channels, such as K + (13)(14)(15)(16)(17)(18), Cl − (19), glutamate receptors (20,21), plasma membrane Ca 2+ (22)(23)(24), and ryanodine receptor Ca 2+ (25,26). However, the underlying biophysical basis of modal gating in the IP 3 R and most other channels remains unknown.…”
mentioning
confidence: 99%
“…The channel is best characterized by its resistance to DHPs and -CTx-GVIA and is shown to coexist with the more common L-type channel observed in various -cells and -cell lines [27,28,35]. Few outside-out patch recordings also provide evidence for a -CTx-GVIA-sensitive Ca 2+ channel with single-channel properties close to the N-type channel described in peripheral neurons [8,24]. The non-L-, non-N-type channel described here has a high probability of being recorded in patches of -CTx-GVIA-treated cells bathed in nifedipine and, therefore, is associated with the Q-like current that contributes to most of the residual non-L, non-N-type current in RINm5F cells [18].…”
Section: Discussionmentioning
confidence: 93%
“…In peripheral neurons the channel activates above 910 mV in 100 mM [Ba 2+ ] o , exhibits a 20 pS singlechannel conductance (1.3 pA at + 10 mV), inactivates weakly during prolonged depolarizations and possesses marked sensitivity to holding potential [24]. Indeed, the neuronal N-type channel also exhibits multiple gating modes with low and high p o [8], small and large conductance and slow and fast inactivation [23] that make any further comparison more complicated and arbitrary.…”
Section: Discussionmentioning
confidence: 99%